2015
DOI: 10.18632/oncotarget.6004
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-152-mediated dysregulation of hepatic transferrin receptor 1 in liver carcinogenesis

Abstract: Over-expression of transferrin receptor 1 (TFRC) is observed in hepatocellular carcinoma (HCC); however, there is a lack of conclusive information regarding the mechanisms of this dysregulation. In the present study, we demonstrated a significant increase in the levels of TFRC mRNA and protein in preneoplastic livers from relevant experimental models of human hepatocarcinogenesis and in human HCC cells. Additionally, using the TCGA database, we demonstrated an over-expression of TFRC in human HCC tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 48 publications
(54 reference statements)
3
45
0
Order By: Relevance
“…It was reported that there were 782,500 new HCC cases and 745,500 incidences of mortality due to HCC worldwide during 2012, of which half were in China (2). Numerous risk factors for HCC patients have been identified, including chronic viral hepatitis B or C infection, chemical exposure, alcohol consumption, obesity, hereditary hemochromatosis and hepatosteatosis (3). At present, the primary therapeutic strategies for HCC are surgical resection, liver transplantation and ablation, and chemotherapy (4).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there were 782,500 new HCC cases and 745,500 incidences of mortality due to HCC worldwide during 2012, of which half were in China (2). Numerous risk factors for HCC patients have been identified, including chronic viral hepatitis B or C infection, chemical exposure, alcohol consumption, obesity, hereditary hemochromatosis and hepatosteatosis (3). At present, the primary therapeutic strategies for HCC are surgical resection, liver transplantation and ablation, and chemotherapy (4).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA‐152 can inhibit cell growth in HepG2 and Hep3B cells . MicroRNA‐152 also suppressed TFR‐1 gene expression in HepG2 . Inhibition of TFR‐1 expression by increased microRNA‐152 in HepG2 cells was associated with decreased intracellular iron and tumorigenicity .…”
Section: Discussionmentioning
confidence: 95%
“…29 MicroRNA-152 also suppressed TFR-1 gene expression in HepG2. 30 Inhibition of TFR-1 expression by increased microRNA-152 in HepG2 cells was associated with decreased intracellular iron and tumorigenicity. 30 In this previous study, based on The Cancer Genome Atlas (TCGA) databases of human HCC, TFR-1 expression increased with the progression of HCC and TFR-1 expression was inversely correlated with microRNA-152.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that TfR has many other biological roles in addition to its primary function of facilitating iron transport and metabolism, such as its profound effect on mammalian cell growth and productivity . TfR expression is normally restricted to a limited number of sites in humans, including basal keratinocytes of the epidermis; islet cells of the pancreas; and parenchymal cells of the liver, testis, and pituitary gland . In healthy lung tissue, airway and alveolar epithelia and bronchial glands do not express TfR .…”
Section: Introductionmentioning
confidence: 99%